Preparation and Characterization Of Co3O4 Nano Powder - Pepi Helza Yanti; Akmal Mukhtar; . Astarina (Jurnal Kimia Valensi, 2015)
Synthesis of Co3O4 has been done using Co(NH3)4.6H2O and KOH as precursors with molar ratio 1:1 M with precipitation method. Several of calcination temperature were done to learn type of mineral phase and crystalinity of Co3O4 synthesized. The XRD analysis revealed that calcination temperature influence crystalinity and mineral phase of Co3O4 prepared and calcination temperature at 700 oC has highest intensity and crystalinity that others. Analysis of particle size was examined using Schererr equation, and the results showed that particle size decrease with calcination temperature. The particle size at  700 oC was = 32.387 nm. Analysis morphology of Co3O4 was examined using SEM technique, and the result revelaed Co3O4 have nearly spherical.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3176.